DNA Technology & biotechnology - Kinnear, Sandy; Neo/SCI Corporation (Rochester, N. Y. : Neo SCI, 2006)
Through this CD-ROM, students will study the latest techniques and applications of biotechnology, such as: electrophoresis; DNA fingerprinting; bacterial transformation; using restriction enzymes and gene splicing to treat disearse and to create transgenic plants and animals. Includes features such as tutorials, lab investigation, self-test, glossory and teacher resources
Title from container
System requirement: Win 98 or higher, Mac 8.6 or higher, including OSX. 128MB RAM
Keywords: DNA; Genetic Engineering -- Study and teaching; Biotechnology -- study and teaching